Tester for spectrometric analog-to-digital converters - A. P. Voiter; M. I. Doronin; A. M. Kovalev; I. O. Maznyj (Ядерна фізика та енергетика)
Software-technical complex for measuring the accuracy parameters of spectroscopic analog-to-digital converters (ADC) by the method of histograms is considered. The complex is based on the special generator of test signals and program for accumulating histograms and calculating the ADC parameters based on them. The complex is intended to be used in the process of preparation for nuclear physics experiments, as well as in the design and manufacture of spectrometric channels. An example of test of two types of spectrometric ADCs with different conversion methods is given.